Respuesta :

Ben

Answer:

[tex]\huge{\boxed{n=-4}}[/tex]

Explanation:

[tex]\begin{array}{cc}\begin{flushright}\text{Divide both sides of the equation by 3.}\end{flushright}&\begin{flushleft}-4n-9=7\end{flushleft}\\\begin{flushright}\text{Add 9 on both sides.}\end{flushright}&\begin{flushleft}-4n=16\end{flushleft}\\\begin{flushright}\text{Divide both sides by -4.}\end{flushrigh}&n=-4\end{array}[/tex]

Answer:

[tex]\Huge \boxed{n=-4}[/tex]

Step-by-step explanation:

First thing you do is divide by 3 from both sides of equation.

[tex]\displaystyle \frac{3(-4n-9)}{3}=\frac{21}{3}[/tex]

Simplify.

[tex]\displaystyle -4n-9=7[/tex]

Then add by 9 from both sides of equation.

[tex]\displaystyle -4n-9+9=7+9[/tex]

Simplify.

[tex]\displaystyle 7+9=16[/tex]

[tex]\displaystyle -4n=16[/tex]

Divide by -4 from both sides of equation.

[tex]\displaystyle \frac{-4n}{-4}=\frac{16}{-4}[/tex]

Simplify, to find the answer.

[tex]\displaystyle 16\div-4=-4[/tex]

[tex]\huge\boxed{\textnormal{N=-4}}[/tex], which is our answer.